2020
DOI: 10.1088/1367-2630/abb43d
|View full text |Cite
|
Sign up to set email alerts
|

Correlations in multithermostat Brownian systems with Lorentz force

Abstract: We study the motion of a Brownian particle subjected to Lorentz force due to an external magnetic field. Each spatial degree of freedom of the particle is coupled to a different thermostat. We show that the magnetic field results in correlation between different velocity components in the stationary state. Integrating the velocity autocorrelation matrix, we obtain the diffusion matrix that enters the Fokker–Planck equation for the probability density. The eigenvectors of the diffusion matrix do not align with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…This reflects similar governing principles and peculiarities observed in polar active models [28,29]. Moreover, the concept of a second temperature successfully describes other systems, ranging from biology to plasma physics [30][31][32][33][34][35][36][37][38][39].…”
supporting
confidence: 53%
“…This reflects similar governing principles and peculiarities observed in polar active models [28,29]. Moreover, the concept of a second temperature successfully describes other systems, ranging from biology to plasma physics [30][31][32][33][34][35][36][37][38][39].…”
supporting
confidence: 53%
“…where the matrix D D D can be derived from Eq. ( 2) 47 or alternatively by using a first-priciple approach 53 , which is given as…”
Section: Steady-state Propertiesmentioning
confidence: 99%
“…The dissipation of energy from the hot to the cold bath occurs on the time scale of velocity correlations which scale inversely with the mass of the particle. The steady state is thus characterised by correlations between different velocity components 53 . This implies that even in the overdamped regime one cannot disregard the inertia-dependent heat loss in the engine.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the behaviour of diffusion systems subjected to an external magnetic field has attracted considerable interest [28][29][30][31][32][33][34][35][36][37][38][39] . It has been shown that Lorentz force due to an external magnetic field induces additional Lorentz fluxes in diffusion systems a Leibniz-Institut für Polymerforschung Dresden, Institut Theorie der Polymere, 01069 Dresden, Germany; E-mail: sharma@ipfdd.de b Technische Universität Dresden, Institut für Theoretische Physik, 01069 Dresden, Germany which are perpendicular to the typical diffusive fluxes 33,35 .…”
Section: Introductionmentioning
confidence: 99%